2022
DOI: 10.1016/j.isci.2021.103675
|View full text |Cite
|
Sign up to set email alerts
|

TORC1 inactivation promotes APC/C-dependent mitotic slippage in yeast and human cells

Abstract: Summary Unsatisfied kinetochore-microtubule attachment activates the spindle assembly checkpoint to inhibit the metaphase-anaphase transition. However, some cells eventually override mitotic arrest by mitotic slippage. Here, we show that inactivation of TORC1 kinase elicits mitotic slippage in budding yeast and human cells. Yeast mitotic slippage was accompanied with aberrant aspects, such as degradation of the nucleolar protein Net1, release of phosphatase Cdc14, and anaphase-promoting complex/cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…Therefore, anaphase cells could potentially disable the mechanism responsible for coordinating the progression of the cell cycle and cellular growth. It has been described that the inactivation of TORC1 increases mitotic slippage after prolonged metaphase block [157], although we have shown that the downregulation of TORC1 in anaphase-arrested cells is unable to promote mitotic exit [156]. Interestingly, TORC1 is inactivated during mitosis in human cells too [158], which might indicate that TORC1 activity during the cell cycle is regulated in a similar way in eukaryotes.…”
Section: Torc1 Regulates Mitosis Progressionmentioning
confidence: 48%
“…Therefore, anaphase cells could potentially disable the mechanism responsible for coordinating the progression of the cell cycle and cellular growth. It has been described that the inactivation of TORC1 increases mitotic slippage after prolonged metaphase block [157], although we have shown that the downregulation of TORC1 in anaphase-arrested cells is unable to promote mitotic exit [156]. Interestingly, TORC1 is inactivated during mitosis in human cells too [158], which might indicate that TORC1 activity during the cell cycle is regulated in a similar way in eukaryotes.…”
Section: Torc1 Regulates Mitosis Progressionmentioning
confidence: 48%
“…Studies have shown that the inhibition of TORC1 kinase can lead to MS in both budding yeast and human cells, ultimately resulting in chromosomal instability. During MS in yeast, several changes occur, including the activation of phosphatase Cdc14, the disintegration of the nucleolar protein Net1, and the degradation of the APC/C-Cdh1-dependent enzyme inhibitor protein and cyclin B during the mid-stage ( Yamada et al, 2022 ).…”
Section: Polyploid Giant Cells In Tumormentioning
confidence: 99%
“…checkpoint proteins regulating DNA repair and mitosis) that have a direct link to CIN (Figure 1). Other miRNAs targeting important structural components such as the cohesin complex (involved in sister chromatid cohesion and the DNA damage response) (reviewed in (Kuru-Schors, Haemmerle et al 2021, Yamada, Morooka et al 2022, could also promote CIN although the direct causal relationship requires further study. miR-22 directly bound and repressed the levels of MDC1 in three different cell lines (HEK293T, HeLa, U2OS) (Lee, Park et al 2015).…”
Section: Micrornas Implicated In Cinmentioning
confidence: 99%